The Clinical Effectiveness of Intralesional Injection of 2% Zinc Sulfate Solution in the Treatment of Common Warts - Essam-elden Mohamed Mohamed; Khaled Mohamed Tawfik; Asmaa Moneir Mahmoud (Scientifica)
Objective. To investigate the clinical efficacy and safety of intralesional injection of 2% zinc sulfate solution in the treatment of common warts. Patients and Methods. One hundred and twenty patients (78 females and 42 males) aged 5–55 years with 225 common warts participated in this prospective monocentric randomized study. All lesions were treated with intralesional injection of 2% zinc sulfate. Results. From 225 warts injected, 135 warts (60%) cured from the first session, 51 warts (22.67%) cured from the second session, and 12 warts (5.33%) cured from the third session. There is no significant relation between improvement and patient’s ages, duration, or number of warts (P<0.05). All patients complained from pain during injection, and all treated lesions showed redness, tenderness, and swelling in the first 3 days after injection. Late complications were postinflammatory hyperpigmentation in 90 patients (75%), scaring in 9 patients (7.5%), and ulceration in 3 patients (2.5%). Recurrence occurred in 3 lesions (1.33%). Conclusion. The clinical data indicate that intralesional injection of 2% zinc sulfate is an effective maneuver in the treatment of common warts; however, its associated complications limit its use.